Highly-integrated power cell for high-power wide band-gap power converters - Espina, Jordi; Ahmadi, Behzad; Empringham, Lee; De Lillo, Liliana; Johnson, Christopher Mark (2017)
The fast switching speeds and low specific conduction losses of wide band-gap semiconductors allow the realisation of high-frequency, high power-density switching converters with dramatically reduced passive component requirements compared to Silicon technology. However, careful attention must be paid to switching cell design to mitigate the effects of circuit parasitics and fast voltage transitions which would otherwise limit the attainable switching speed and lead to increased levels of EMI. This paper presents a modular, power-cell solution which allows the creation of any two-level topology converter. The cell structure enables fast switching of wide bandgap semiconductor devices while allowing high power converters to be fabricated using multiple, smaller commutation cells. Close integration of semiconductor dies, decoupling capacitors, gate drives and an output filter with a single ceramic substrate to act as the thermal path allows dramatic increases in power density without compromising converter performance